Performance of PT. Bank BTPN Syariah, Tbk in a Covid-19 Pandemic Situation - Koesmawan Koesmawan; Ardiansyah Ardiansyah (Budapest International Research and Critics University, 2022)
Covid-19 has counted thousands of Indonesians and millions of people around the world who died because the Covid-19 virus spread so quickly and had an impact on the economy in Indonesia, especially in the banking industry and non-banking industry. The purpose of this study is to test performance differences such as Assets, Third Party Funds (DPK), Financing, Profit and Non-Performing Financing (NPF) with the Statistical Package for the Social Sciences (SPSS) analysis method for the period 2019 and 2020 in the Covid-19 pandemic situation. 19 and tested management targets for 2020 using the Analytical Network Process – Benefits, Opportunities, Costs, Risks (ANP-BOCR) method in the COVID-19 pandemic situation. The results of this study indicate the performance of PT. Bank BTPN Syariah, Tbk in the Covid-19 pandemic situation in 2020 still looks good.